A RANDOMISED CONTROL TRIAL ON CEREBRO VASCULAR ACCIDENT PATIENTS WITH REFERENCE TO AETIOLOGY AND MANAGEMENT: 24 WEEKS, SINGLE-CENTER, PROSPECTIVE OBSERVATIONAL PILOT STUDY - K, LEELA PRASAD; KAREEMULLA, SHAIK; K, ALIYA FIRDOSE; S, YASMEEN (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objectives: Stroke is one of the leading causes of death and long-term disability in world. Stroke is an important cause of premature death and disability in low-income and middle-income countries like India, largely driven by demographic changes and enhanced by the increasing prevalence of key modifiable risk factors. The main aim of our study was to assess the clinical profile with special reference to the etiology of the condition, the management, and drug utilization review. Methods: This is a hospital-based prospective observational randomized control trial which was conducted for a period of 6 months at Government General Hospital, Rajiv Gandhi Institute of Medical Sciences, Kadapa. Seventy-five patients were recruited based on study criteria. The data were analyzed and summarized as frequency and percentage by GraphPad Prism software using Microsoft Excel. Results: In a total of 75 patients, it was found that 45 and 30 patients were female. Maximum number of patients (i.e. 36 patients) belonged to 51–60 years age group. We observed that 52 patients were suffering from ischemic stroke, 21 patients were suffering from transient ischemic stroke, and only 2 patients were suffering from ischemic stroke and transient ischemic stroke. Among 75 patients studied, hypertension (62%), diabetes mellitus (28%), smoking (33%), and alcohol (33%) were the risk factors. Conclusion: In this study, ischemic stroke was most prevalent. Hypertension, that is, increase of blood pressure considered as one of the important and major risk factors for stroke occurrence and recurrence. Proper management includes non-pharmacological (physiotherapy) along with pharmacological treatment that included cardiovascular system drugs such as hypolipidemics, cognition enhancers, anticoagulants, and antihypertensive therapy.